EVALUATION OF SANITARY HYGIENIC CONDITIONS OF REFRIGERATORS IN THE MUNICIPALITY OF PARAIPABA-CE - do Nascimento Souza, Alexandra; Gisele Carneiro da Silva, Maria; Alves da Silva Rios, Danielle; Soares Damasceno, Leandro; Gislaine Lira Magalhães de Oliveira, Ana; Raina Rabelo, Vitória; de Cássia Rufino de Sousa Miranda, Rita; Luana Guillen Pumar, Nayara; Maria de Morais, Vania; Galeno Araújo, Cíntia (Health and Society, 2024)
The consumer increasingly associates quality food with safe food. Consequently, major brands publicize their products by emphasizing quality, always associating them with strict control of the production system. The objective of the present work was to evaluate the hygienic-sanitary conditions of refrigerators located in the municipality of Paraipaba (CE). This was a descriptive case study with quantitative approach conducted in three refrigerators in which it was coded as F 01, F 02 and F 03. To obtain the data, a Chec Klist list was used as resolution no. 216 of 2004, to evaluate the buildings, facilities, equipment, furniture and utensils and their hygiene, manipulators, raw materials and packaging, food preparation, storage and exposure to the consumption of prepared food. The results of fridge 01 showed a total percentage of 67.56% of conformities and 32.44% of nonconformities, refrigerator 02 presented 67.56% of conformities and 32.44% of nonconformities, refrigerator 03 presented 70.27% of conformities and 29.73% of nonconformities. In this way, the awareness and training of manipulators with guidance on basic health and hygiene and good practices in food manipulation is necessary.